Frekuensi konsumsi dan kontribusi zat gizi makro jajanan Korea di pusat kuliner Yogyakarta - Khofifah, Hesti; Ayuningtyas, Cita Eri; Ramadhani, Khairunisa (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2024)
Consumption frequency and nutritional contribution of Korean snacks in culinary centers in YogyakartaBackground: The trend of Korean snacks in Indonesia makes people more consumptive. The Korean wave influences this through the popularity of K-pop and K-drama artists from social media platforms. The increasing consumption pattern of Korean snacks has made people less aware of the frequency limits of consumption and the nutritional content of Korean snacks. Objectives: This study aims to see the difference between consumption frequency and nutritional intake and analyze Korean snacks' nutritional contribution to visitors to Yogyakarta's culinary centers.Methods: This research is a quantitative descriptive design study with a cross-sectional approach involving 110 subjects with an average age of 18-30 years. The subject selection used the accidental technical sampling method. The questionnaire using the SQ-FFQ has been validated in previous research. The frequency of consumption of Korean snacks is categorized into three, namely rarely (1-3x/month), sometimes (1-2x/week), and often (≥3x/week). Data collection was carried out by distributing questionnaires directly at the research location. Data analysis used univariate and bivariate analysis with the one-way ANOVA test. Results: The characteristics of respondents are that the majority are female (89.1%). The average consumer age group is 21-30 (56.3%). The distance from the residence and location of the culinary center is mainly in the distance category > 3 km (63.6%). The contributions of energy (44.5%), carbohydrates (64.5%), protein (73.6%), and fat (67.3%) from Korean snacks exceeded the intake limit. There is a significant difference between consumption frequency and nutritional intake of Korean snacks (p<0.05).Conclusions: Frequency of consumption shows a significant difference between the contribution of energy and macronutrients. The contribution of nutrients to visitors was found still to exceed the limit for food intake from snacks.